Poplar Tree Improvement Programme - Chaturvedi, A. N.; Rawat, B. S. (Indian Forester, 1994)
Populus deitoides clones were introduced in India in 1952 to increase the availability of wood for match and plywood industries. Clones introduced. from U.K. and Europe did not perform well while the clones from U.S.A and Australia grew well. By 1970, Poplars started being planted under irrigated conditions and grew faster than any other indigenous or exotic species. Clones G-3, G-48, D-100 and D-121 presently form the backbone or the Poplar planting programme which has spread in farm-lands. To increase the genetic base the production of indigenous clones and introduction of more clones from suitable area of U.SA was carried out. The crosses of P. deltoides with Populus ciliata have also been produced and are being tried at several locations. Large number of clones obtained from U.S.A. also include cuttings from wild populations. These are under testing and some of these clones are promising. Cutting from male and female clones of Populus euphratica obtained from Pakistan are growing well at TERI field research station and are in flower at present. The genetic base has now been widened and newer clones will continue to be available for several generations. The effort for selecting, new clones and their testing must continue.